DNA Barcoding Analysis of Betok Fish (Anabas testudineus) from Kampar, Riau Based on Cytochrome Oxidase Subunit I (COI) - Rahmah, Miftahul; Hasibuan, Aldy Riau Wansyah; Melia, Tisha; Al Khairi, Hapiz; Roslim, Dewi Indriyani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Ikan betok (Anabas testudineus, Bloch 1792) is one of fishes which is a member of family Anabantidae. Betok is an endemic fish in Riau Province. The scientific study about DNA barcoding of betok fish is still rarely. This research aims to analyze the DNA barcode sequence of cytochrome c oxidase I (COI) on betok fish. Methods were used in this study such as sampling, total DNA extraction, PCR, electrophoresis, sequencing and data analysis. The COI sequence studied had size of 694 bp. The BLASTn analysis showed that the betok fish had the highest similarity of 99.7% with A. testudineus and the lowest 93.00% with A. cobojinus. There was one nucleotide that characterize the betok fish based on the COI sequence namely nucleotide number 309. This study may enrich the DNA barcode database of betok fish in GeneBank.